Media Development Based on Equipment Modifications in Table Tennis Games for Elementary Students: Bahasa Inggris - Ignasius Ivan Kurnia Ndruru; Agung Sunarno; Sanusi Hasibuan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to introduce the game of small ball to elementary school students specifically in table tennis with a modification of the tool in the form of a table size that fits the body of elementary school children. This research method is development (Research and Development). The population of the research is sixth grade students at State Elementary Schools in Patumbak District, Deli Serdang Regency. The validation results of the expert questionnaire assessment were declared valid and usable with the percentage of media experts obtained at 83% in the valid category. Meanwhile, the percentage value from the meter expert was obtained at 80% in the valid category. Results of the questionnaire instrument assessment given to students during initial testingIt is known that the score obtained was 82% which was in the 80%-100% interval in the valid category. Results of the questionnaire instrument assessment given to students at the time large scale trialsIt is known that the score obtained was 83% which is in the 80%-100% valid category interval.So it can be said that teaching media products based on tool modification in table tennis games meet the criteria or are suitable for use by elementary school students as learning media. Conclusion, 1.The ideal size for mini table tennis has been created for class VI students at State Elementary Schools in Patumbak District. 2. Mini table tennis can be used by teachers and students in the physical education learning process in elementary schools.